Conversión bacteriológica en casos nuevos de tuberculosis pulmonar con bacilo de Koch positivo (BK+) en la zona 7 - Ecuador - Capa Alvarado, Jenny Elizabeth (2014)
This research work titled "BACTERIOLOGICAL CONVERSION IN NEW CASES OF PULMONAR TUBERCULOSIS WITH BACILLUS OF KOCH POSITIVE (BK+) IN THE 7 ZONE – ECUADOR” makes part of the Macro – Project titled “BACTERIOLOGICAL CONVERSION, ASSOCIATED TO CO-MORBIDITY AND PROVISION OF SERVICES IN NEW CASES OF PULMONAR TUBERCULOSIS BK+ IN SEVEN ZONE - ECUADOR” which was developed by means of a descriptive study, whose main objective is to determine the bacteriological conversion in new cases of pulmonary tuberculosis Bk+ in the provinces of the 7 Zone - Ecuador, to establish the bacteriological conversion in the provinces of the 7 Zone and to determine time and bacteriological conversion, during the antifímico treatment of the new cases of pulmonary tuberculosis during the period 2013. The information was obtained through the starting and evaluation, which that was applied to the patients who are under the anti-tuberculosis treatment in the different operative units of health and entered to the program of the PCT. The tabulation and the analysis was developed through tables, which indicates that the total number of cases diagnosed with pulmonary tuberculosis in the 7 Zone during the year 2013, is two hundred and seventy one new cases, presenting greater incidence in the El Oro Province followed by Loja and Zamora with a minor number of cases, predominating in the masculine sex between 15 and 25 years old, specially to the single civil state. Through monthly monitoring of patients, was determined that in the first month of control they got 87% of conversion, which becomes increased during the whole first phase, probing in this way that once ended the treatment in the sixth month of control, the totality of the new cases of tuberculosis have reached 100% of the bacteriological conversion. Key Words: Pulmonary Tuberculosis, Bacteriological Conversion.